2019
DOI: 10.1063/1.5117504
|View full text |Cite
|
Sign up to set email alerts
|

Radiation transport and scaling of optical depth in Nd:YAG laser-produced microdroplet-tin plasma

Abstract: Experimental scaling relations of the optical depth are presented for the emission spectra of a tin-droplet-based, 1-lm-laser-produced plasma source of extreme-ultraviolet (EUV) light. The observed changes in the complex spectral emission of the plasma over a wide range of droplet diameters (16-65 lm) and laser pulse durations (5-25 ns) are accurately captured in a scaling relation featuring the optical depth of the plasma as a single, pertinent parameter. The scans were performed at a constant laser intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…Instead, a single-temperature, single-density approach is here employed. Indeed, recent experiments by Schupp et al 22 have indicated that a dominant fraction of the EUV emission may be produced in such a quasi-stationary 24 single-density, singletemperature region. For such a medium, the spectral flux I λ can be determined using the simple solution I λ ¼ B λ 1 À expðÀτÞ ½ , with the optical depth τ defined as the product between α λ and the transport path-length L. The temperature of the opacities are chosen such that the calculated charge state contributions matched the observed one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, a single-temperature, single-density approach is here employed. Indeed, recent experiments by Schupp et al 22 have indicated that a dominant fraction of the EUV emission may be produced in such a quasi-stationary 24 single-density, singletemperature region. For such a medium, the spectral flux I λ can be determined using the simple solution I λ ¼ B λ 1 À expðÀτÞ ½ , with the optical depth τ defined as the product between α λ and the transport path-length L. The temperature of the opacities are chosen such that the calculated charge state contributions matched the observed one.…”
Section: Resultsmentioning
confidence: 99%
“…The tenfold decrease in laser wavelength λ increases the critical plasma electron density n c by two orders of magnitude, n c ∝ λ −2 . This higher critical density causes EUV radiation to be created in plasma regions of higher density, and with overall larger optical depth 22 . Significant self-absorption of the emitted radiation in such dense, partially opaque plasma could lead to a broadening of the spectral emission out of the 2% bandwidth of interest, reducing efficiency.…”
mentioning
confidence: 99%
“…The Nd:YAG-laser-produced tin plasma relevant for the production of extreme ultraviolet light is hot (∼30 eV) and dense (∼10 21 e − cm −3 ) (see, e.g., Refs. [62,72,73]). At the laser intensity of 1.7 × 10 11 W/cm 2 , used in our experiments, given the density set by the laser wavelength [1], the temperature of the plasma produces a charge-state distribution containing mostly Sn XII-Sn XV ions [73] that is optimal for emitting EUV light at 13.5 nm [62,72].…”
Section: Diagnostics Of the Afterglow Of Laser-produced Plasmamentioning
confidence: 99%
“…[62,72,73]). At the laser intensity of 1.7 × 10 11 W/cm 2 , used in our experiments, given the density set by the laser wavelength [1], the temperature of the plasma produces a charge-state distribution containing mostly Sn XII-Sn XV ions [73] that is optimal for emitting EUV light at 13.5 nm [62,72]. After the laser pulse ends, the plasma quickly cools down while continuing its free, quasispherical expansion [74].…”
Section: Diagnostics Of the Afterglow Of Laser-produced Plasmamentioning
confidence: 99%
“…The scaling of the here relevant inverse bremsstrahlung absorption coefficient k L ∝ λ 2 n 2 e , with wavelength λ and electron density n e indicates that shorter wavelength light is absorbed less efficiently at equal plasma density but because of the higher critical electron density (n c ∝ λ −2 ), the shorter wavelength laser light can penetrate into denser plasma regions leading to an overall increased absorption of the laser light, with the absorption taking place in regions of higher emitter and absorber density. This may benefit the obtainable source brightness but an associated increase in optical depth [32,33] leads to increased broadening of spectral features outside the in-band region relevant for EUV lithography. This broadening may limit the obtainable CE.…”
Section: Introductionmentioning
confidence: 99%